Efisiensi Produksi Kantong Kraft Melalui Pengurangan Waste Dengan Lean Manufacturing Pada PT IKSG - Satrio Bagus Utomo; Rizky Dermawan; Ratih Mukti Azhar (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
PT Industri Kemasan Semen Gresik faces the problem of Waste in the kraft bag production process that exceeds the standards set by the company. This condition causes non-optimal production results so that additional time is needed for repair and re-production to meet customer demand. This study aims to minimize Waste and improve the efficiency of the kraft bag production process at PT Semen Gresik Packaging Industry using the Lean Manufacturing approach. The method used is descriptive quantitative, relying on primary data from observations, interviews, and surveys, as well as secondary data from internal company documents. Analysis techniques include the use of Value Stream Mapping (VSM), Value Stream Analysis Tools (VALSAT), and Root Cause Analysis (RCA) through the Fishbone and 5 Why's methods, as well as assessment of Waste with a Likert scale. The results showed that several types of Waste such as Overprocessing, Defects, and Motion are the main Wastes that hamper production efficiency. Proposed improvements were made through work layout adjustments and the application of Total Productive Maintenance to improve the performance of the production system. The overall results show that the Lean Manufacturing approach is effective in systematically identifying and eliminating Waste to improve the efficiency of the production process.